W WORKSHOP DAN PENDAMPINGAN IDENTIFIKASI PRODUK UNGGULAN JURUSAN ATPH SMKN 1 BORONG KABUPATEN MANGGARAI TIMUR - Noywuli, Nicolaus; Kaleka, Marten Umbu; Uran, Maria. A. D.; Igniosa Taus; Victoria Ayu Puspita; Karina Dhena Goda (LPPM UNINUS, 2024)
Borong 1 Public Vocational High School is one of the schools supported by Michael D. Ruslim from the Astra Education Foundation in East Manggarai Regency, East Nusa Tenggara. This school was prepared to become a leading school in East Manggarai with assistance from the Flores Bajawa Agricultural College. The aim of the workshop and product identification assistance in the agribusiness department of food crops and horticulture is to prepare teachers to educate students with factory-based learning. The results of this identification will be internalized and then used to develop a harmonized curriculum that will be used as learning material at SMKN 1 Borong with the name BMW Curriculum (work, continuing studies, and entrepreneurship). The method used in this community service includes workshops and mentoring for target teachers. From the results of this community service, it can be concluded that this coaching was quite successful, as the workshop participants were very enthusiastic about the training activities. This can be seen from the percentage of target teacher attendance, which reached 100%, along with the presence of supervisory coordinators who supported this program. Apart from that, the results of the assistance show that the superior products that are characterized by the characteristics produced are tomatoes, cassava tubers, quality pineapples, superior coffee beans, and quality cocoa beans. Keywords: community service, featured product, Workshop